PENGARUH CUSTOMER EXPERIENCE DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN ULANG DENGAN PERCEIVED VALUE SEBAGAI VARIABEL INTERVENING (STUDI DI HOTEL SANSET BEACH JEPARA) - Muhammad Zakiy' Askari; Nurul Komariyatin (Journal Economic Management and Business, 2026)
The purpose of this study is to examine the effect of customer experience and brand image on repurchase intention with perceived value as an intervening variable (a study at Sanset Beach Hotel Jepara). This research is classified as descriptive quantitative research. The study was conducted at Sanset Beach Hotel Jepara. The population consisted of all guests staying at Sanset Beach Hotel Jepara, with the exact number unknown. The minimum sample size was determined using Hair’s formula, resulting in 85 respondents who were hotel guests. The research method was based on the positivism paradigm. Data were collected using a questionnaire. Data analysis was carried out using SmartPLS 4 through two main stages: (1) Measurement Model Evaluation (Outer Model) and (2) Structural Model Evaluation (Inner Model). The findings indicate that all hypotheses were accepted. Customer Experience and Brand Image have a positive and significant effect on Repurchase Intention as well as on Perceived Value. Perceived Value also has a positive and significant effect on Repurchase Intention and mediates the relationship between Customer Experience and Brand Image on Repurchase Intention. These findings confirm that enhancing customer experience and strengthening brand image can increase consumers’ perceived value, which in turn encourages repurchase intention